The Formation Mechanism of Electrospun Beaded Fibers: Experiment and Simulation Study. Issue 1 (January 2023) - Ge, Cheng; Zheng, Yuansheng; Liu, Kai; Xin, Binjie; Li, Masha; All Amin Newton, MD.
This research examined the influence of solution concentration on Taylor cone morphology, jet behavior, fiber surface morphology, and the impact of spinning voltage on the microbead shape of the beaded fiber. The straight jet length, envelope cone, whipping frequency of the electrospun jet, and Taylor cone morphology were studied using the images captured by a high-speed photography camera. According to the findings, higher solution concentrations result in longer straight jet lengths, smaller envelope cones, and lower whipping frequencies. Scanning electron microscopy was used to ascertain the diameter and surface morphology of polystyrene fibers, revealing that fibers spun with higher solution concentrations had larger diameters. In contrast, low concentration solutions receive more electric field forces due to higher conductivity. The jet tends to break, and fibers with the beads-on-a-string morphology form. Furthermore, the influence of voltage on microbead shape has been further examined using the simulation software COMSOL. As the spinning voltage increases, the jet's stretching impact is more prominent, and the bead shape gradually changes from nearly circular to spindle-shaped.